2020
DOI: 10.1093/nutrit/nuaa008
|View full text |Cite
|
Sign up to set email alerts
|

From carotenoid intake to carotenoid blood and tissue concentrations – implications for dietary intake recommendations

Abstract: There is uncertainty regarding carotenoid intake recommendations, because positive and negative health effects have been found or are correlated with carotenoid intake and tissue levels (including blood, adipose tissue, and the macula), depending on the type of study (epidemiological vs intervention), the dose (physiological vs supraphysiological) and the matrix (foods vs supplements, isolated or used in combination). All these factors, combined with interindividual response variations (eg, depending on age, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
163
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 157 publications
(183 citation statements)
references
References 281 publications
10
163
0
10
Order By: Relevance
“…These carotenoids profile proportions follow the same pattern in dietary intake as in blood (β-carotene > β-cryptoxanthin > α-carotene). There was a correlation between α-carotene and β-carotene in dietary intake and blood concentrations as in other studies [56], as can be expected because both are supplied by the major dietary food contributors (Table 3) and are often found in the same foods [3]. In contrast, β-cryptoxanthin is mainly supplied by red-orange fruits and juices [3,5].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…These carotenoids profile proportions follow the same pattern in dietary intake as in blood (β-carotene > β-cryptoxanthin > α-carotene). There was a correlation between α-carotene and β-carotene in dietary intake and blood concentrations as in other studies [56], as can be expected because both are supplied by the major dietary food contributors (Table 3) and are often found in the same foods [3]. In contrast, β-cryptoxanthin is mainly supplied by red-orange fruits and juices [3,5].…”
Section: Discussionsupporting
confidence: 81%
“…A similar pattern was found in the mean values of the compiled studies, 60% β-carotene, 25% β-cryptoxanthin and 15% α-carotene. Although the proportions of β-cryptoxanthin and α-carotene in blood are similar in some studies [39,45,55], in others, β-cryptoxanthin concentration is higher than that of α-carotene in blood but not in the dietary intake [56], or the percentage of blood β-cryptoxanthin is half that of α-carotene [48] and β-cryptoxanthin is slightly higher than β-carotene [37]. These differences are clearly seasonal in some population groups [8,56] but could also be due to factors related to the subjects included in the studies since, although in general, no characteristics were reported that could affect carotenoid metabolism, there could be exceptions.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, highly dosed supplemental use of β-carotene has been correlated with smokers with negative outcomes, increasing total mortality ( 9 , 10 ) and enhancing lung cancer rate ( 11 , 12 ) . While nutritional relevant levels of β-carotene have been in the range of 0·1–8·8 (median 3·9) mg/d as reviewed recently ( 13 ) , isolated administered β-carotene at rather high doses (>30 mg/d) may initiate previously mentioned negative effects. The reasons for these negative effects are not entirely clear but indicate that such high levels of β-carotene, which are usually non-harmful, may affect precancerous lesions, which are a hallmark of cancer development, and result from smoking ( 14 ) .…”
Section: Introductionmentioning
confidence: 98%